2019
DOI: 10.1111/mcn.12796
|View full text |Cite
|
Sign up to set email alerts
|

Age of introduction of complementary feeding and overweight in adolescence and adulthood: A systematic review

Abstract: Recent studies on early infant feeding suggest that the type of diet and age of starting complementary foods may have a positive correlation with overweight in adolescence and adulthood. This study aimed to systematically review the evidence on the relationship between the age of introduction of complementary feeding and excess weight in adolescence and adulthood (PROSPERO: CRD42017067764). The preferred reporting items for systematic reviews and meta-analyses standards were used as a reference. Articles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…Timing of CF introduction could contribute to childhood obesity, although previous studies showed inconsistent associations. [12][13][14][15] Systematic reviews suggested no clear association between CF introduction with children's obesity risk, with the exception of solid food introduction before 4 months, 14,16 which has been associated with greater obesity risk. Limitations of studies thus far include small sample sizes, a lack of inclusion of important confounders (eg, breastfeeding or formula feeding and maternal and paternal BMI), and the lack of longitudinal assessment of outcomes, especially up to adolescence.…”
mentioning
confidence: 99%
“…Timing of CF introduction could contribute to childhood obesity, although previous studies showed inconsistent associations. [12][13][14][15] Systematic reviews suggested no clear association between CF introduction with children's obesity risk, with the exception of solid food introduction before 4 months, 14,16 which has been associated with greater obesity risk. Limitations of studies thus far include small sample sizes, a lack of inclusion of important confounders (eg, breastfeeding or formula feeding and maternal and paternal BMI), and the lack of longitudinal assessment of outcomes, especially up to adolescence.…”
mentioning
confidence: 99%
“…Feeding plays a fundamental role in adequate growth and development in early childhood 1 . Given the impact of feeding on infant morbidity and mortality 2 and the influence of childhood feeding practices on health in adulthood 3,4 , complementary feeding is an undeniably relevant theme for the public health agenda. This highlights the need for policies to promote healthy feeding in childhood to support and protect breastfeeding and adequate complementary feeding [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Although studies have investigated the relationships between early CF introduction at age < 4 months and excessive weight gain in children, these studies have yielded inconsistent results. For example, several studies have documented meaningful links between early CF introduction and excess weight gain, 6,[11][12][13] whereas others have found no association between the time of CF introduction and excessive weight gain in children. [13][14][15][16] Moreover, studies assessing these associations have had important limitations, including small sample sizes, failure to account for important confounders by methodological issues and lack of longitudinal assessment.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Moreover, studies assessing these associations have had important limitations, including small sample sizes, failure to account for important confounders by methodological issues and lack of longitudinal assessment. 12,13,15,17 The present study evaluated the potential associations between timing of CF introduction and childhood body mass index (BMI) by analysing a large-scale, population-based nationwide cohort dataset in Korea. Data were derived from a nationwide cohort study that included all Korean children born in 2008 and 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation